(untitled) (Journal of Geography, Meteorology and Environment, 2020)
This paper examines the challenges of quarrying activities on sustainable quality water resources in Abakaliki and environs and the socio-economic implications of the effects on the people in order to find strategies to mitigate the effects. Data collection yielded 7 water samples and administration of 400 copies of questionnaires, interviews and photographs from 5 quarrying sites and one control site. Water samples were analyzed for physico-chemical properties at PRODA, Enugu. Analyses of data were by descriptive statistics, correlation and Principal Components Analysis (PCA). The result showed that the methods of quarrying and crushing of the rock lumps were generating dust and acidic waste water pollutants through runoff into the surrounding surface water bodies. PCA identified that pollution makes the water hard, low in oxygen and contains heavy metals above permissible limits. Parameters like Pb, As, Fe, Cu, Zn, Cd which contributed in pollution of the waters were found to affect aquatic plants, animals, human health and the ecosystem. Remediation was advanced as plausible mitigation measure to stem the increasing pollution trend, ensure safety of the environment, man and the attainment of the SDGs.